Quality Evaluation of Frigate Mackarel Fish Pindang and Flying Fish Pindang from Fish Processing Centers in Kusamba Village, Klungkung Regency, Bali - I Gde Suranaya Pandit (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Pindang is one of the traditional processed products derived from fish. Various types of fish can be processed into pindang, namely frigate mackerel fish, flying fish, sardinella, tuna, mackarel, cakalang and milkfish. Various types of fish cause various types of processing are carried out by the community and will eventually produce different quality. The purpose of this study was to evaluate and analyze the chemical, microbiological and organoleptic quality produced. Quality evaluation in comparative experimental research by comparing the quality of frigate mackarel fish pindang with flying fish. Parameters evaluated included chemical parameters, namely water content, salt content, histamine content, total volatile bases content, and trimethylamine content, microbiological parameters such as the number of bacteria, as well as organoleptic parameters including appearance, smell, texture, and taste. Based on the results of the study, the quality of frigate mackerel pindang with flying fish had significantly different qualities, especially in chemical assessment and organoleptic assessment.